Effect of Antimicrobial Agents on Modification of Coir. (2016) - Sumi, S.; Unnikrishnan, N.; Mathew, Lea
Abstract: Coir yarns were coated with three natural anti-microbial agents - Cashew Nut Shell Liquid (CNSL), neem oil and tulsi oil for improving its hydrophobicity, tensile strength and biological resistance. Microbial degradation study was performed with A. niger as test organism. The results indicated that coating of coir yarns was capable of increasing tensile strength by 17% and reducing moisture absorption by 34%. Microbial activity of CNSL coated coir yarns was reduced to 95%. Coating with neem oil was found to be less effective while coating with tulsi oil adversely affected the physical and engineering properties of coir.